State-of-the-arts methods for studying factors driving the utilization of open science resources - Le Thi Tuyet Trinh; Nguyen Thi Thu Hang; Le Minh Cuong; Ngo Van Dinh; Hoang Khanh Linh; Do Thi Trinh; Nguyen Thuy Phuong Tram; Ho Nguyen; Manh-Tung Ho (MethodsX, 2025)
The open science movement aims to democratize essential scientific values, including rigor, transparency, availability, and replicability. However, open science resources are still often underutilized. A comprehensive evaluation of the factors influencing the use of these resources is urgently needed. This evaluation not only supports evidence-based policymaking to help researchers thrive in a highly competitive academic environment but also prevents misunderstandings and confusions related to emerging scientific practices. This article presents a survey-based framework for understanding the factors that affect the ability to utilize open science resources. To achieve this, we will integrate relevant factors such as capabilities, attitudes, perceived costs and benefits, cultural and institutional influences, and alignment of values into our analytical framework. These factors are derived from significant theories that have been applied to study the acceptance and use of information systems: the Theory of Planned Behavior, Self-Determination Theory, the Unified Theory of Technology Use and Acceptance, Self-Efficacy Theory, and the value-filtering model known as Mindsponge Theory.We will briefly introduce the key elements of these frameworks and discuss their applications in the context of utilizing open science resources as well as in the broader context of innovation adoption. Furthermore, we argue that elements from these models significantly overlap and complement one another. Therefore, to thoroughly evaluate the factors affecting the utilization of open science resources, it is essential to coherently combine aspects from these models into a unified analytical framework.